2016
DOI: 10.1210/jc.2015-3889
|View full text |Cite
|
Sign up to set email alerts
|

Pheo-Type: A Diagnostic Gene-expression Assay for the Classification of Pheochromocytoma and Paraganglioma

Abstract: The Pheo-type gene-expression assay is a reliable method for predicting PPGL genotype using routine diagnostic tumor samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…To our best knowledge, AMH has not been reported in these cases. In a recent study, the authors have shown that MAX -related PHEO can contain distinct morphological tumor regions with different gene-expression patterns [12] .…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, AMH has not been reported in these cases. In a recent study, the authors have shown that MAX -related PHEO can contain distinct morphological tumor regions with different gene-expression patterns [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The kinase signalling subgroup, includes characteristic mutations in REarranged during Transfection (RET) in Multiple Endocrine Neoplasia type 2 (MEN2), Neurofibromatosis type 1 (NF1), transmembrane protein 127 (TMEM127), MYC associated factor X (MAX), EGLN1 (PHD2), KIF1 and IDH1 [ 6 ]. Our group has recently described a technique for assigning tumours into these subcategories [ 7 ]. PCCs may coexist with other tumour types in MEN2A, MEN2B, VHL and NF1.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we extended our study to a more in‐depth analysis of lincRNAs in the clinically relevant molecular subtypes of PCPG. Previously, a gene expression signature was proposed as marker of PCPG subtypes . However, employing machine‐learning algorithms, we found lincRNA signature that serves as a high‐precision marker of aggressive or nonaggressive PCPG subtypes, which could be used in future diagnostic assays.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, a gene expression signature was proposed as marker of PCPG subtypes. 37 However, employing machine-learning algorithms, we found lincRNA signature that serves as a high-precision marker of aggressive or nonaggressive PCPG subtypes, which could be used in future diagnostic assays. The high precision of this lincRNA signature may be attributed to the fact that lincRNA expression is more tightly regulated.…”
Section: Discussionmentioning
confidence: 95%